Design, Implementation and Characterization of Cavity for Absolute Radiometer - Carlesso, Franciele; Vieira, Luis E. A.; Berni, Luiz A.; Savonov, Graziela da S. (Frontiers in Physics, 2021)
Absolute radiometers are based on electrical substitution radiometers, which compare optical and electrical power. The same physical principle applies to standard reference detectors operating at cryogenic temperatures and room temperature radiometers for total solar irradiance (TSI) measurements. Both types rely on the cavity with an internal low-reflectance coating to absorb incident radiation similar to a black body. The cavity shape design requires an analysis of the coating reflection properties. Like many materials, ultra-black Ni-P exhibits a mixture of diffuse and specular reflection that depends on the angle of incidence of light in the pores. We employed ray-tracing software to study the impact of the geometry on the absorptivity and distribution of the scattered rays. We describe the scattering model of the black coating in terms of the bidirectional reflectance distribution function. Also, we examined the difficulties of Ni-P electroless deposition and blackening inside the cavity. The measured absorptance of the cavity showed some discrepancies of the simulated absorptance mostly probably due to Ni-P non-uniformity coating.